2012
DOI: 10.1002/biot.201200170
|View full text |Cite
|
Sign up to set email alerts
|

Applying high‐throughput methods to develop a purification process for a highly glycosylated protein

Abstract: Micro-scale chromatography formats are becoming more routinely used in purification process development because of their ability to rapidly screen large number of process conditions at a time with minimal material. Given the usual constraints that exist on development timelines and resources, these systems can provide a means to maximize process knowledge and process robustness compared to traditional packed column formats. In this work, a high-throughput, 96-well filter plate format was used in the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…High-throughput methods enable the rapid screening of suitable operation parameters [23][24][25][26]; although these methods are more popular for establishing chromatography methods, for nonchromatography methods it is simple to use high-throughput microtiter-plate technology to find suitable conditions. High-throughput methods enable the rapid screening of suitable operation parameters [23][24][25][26]; although these methods are more popular for establishing chromatography methods, for nonchromatography methods it is simple to use high-throughput microtiter-plate technology to find suitable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput methods enable the rapid screening of suitable operation parameters [23][24][25][26]; although these methods are more popular for establishing chromatography methods, for nonchromatography methods it is simple to use high-throughput microtiter-plate technology to find suitable conditions. High-throughput methods enable the rapid screening of suitable operation parameters [23][24][25][26]; although these methods are more popular for establishing chromatography methods, for nonchromatography methods it is simple to use high-throughput microtiter-plate technology to find suitable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of scale down chromatography studies have been well described in the literature. Some more recent examples are included .…”
Section: Workflow: What Is Everyday Htpd?mentioning
confidence: 99%
“…The purities of all purification methods are statistically similar to the baseline-positive control from analysis by nonreduced CE-SDS, reduced CE-SDS, RP-HPLC, HP-SEC, HP-CEX, and N-Glycan. Sanaie et al reported a discrepancy between the resin-plate performance to that of a packed column in terms of glycoform distribution, but this was attributed to lower theoretical plates for the slurry method, which would not be a concern for affinity chromatography [26]. Variation is greater for the high-throughput formats than the baseline column format for some assays, but not all, indicating reasonable precision for the HTS formats relative to the baseline column format.…”
Section: Analytical Comparabilitymentioning
confidence: 99%